1971
DOI: 10.5254/1.3547400
|View full text |Cite
|
Sign up to set email alerts
|

Tread Wear and Wet Skid Resistance of Butadiene-Styrene Elastomers and Blends

Abstract: 1. Car, wheel position, driver, inflation pressure, and shoulder drop have a statistically significant effect upon wear loss and need to bo taken into consideration before material factors affecting wear can be studied. 2. Variations in macrostructure of the polymers are not found to have a significant effect on wear as compared to microstructure variations. 3. At least two material factors control wear loss of tire treads. 4. When polymers are tested near their glass transition temperature (within 80° C), wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1973
1973
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Increase in T g indicates a reduction in the rate of relaxation processes in the polymer and consequently leads to a reduction in elasticity. In turn, low elasticity of the rubbers results in an improvement in the wet road holding of the tyres, with an appreciable reduction in wear resistance [12][13][14]. These conclusions are entirely consistent with our findings.…”
Section: A P -Plasticity; R -Elastic Recovery; F C -Cohesive Strengthsupporting
confidence: 89%
See 1 more Smart Citation
“…Increase in T g indicates a reduction in the rate of relaxation processes in the polymer and consequently leads to a reduction in elasticity. In turn, low elasticity of the rubbers results in an improvement in the wet road holding of the tyres, with an appreciable reduction in wear resistance [12][13][14]. These conclusions are entirely consistent with our findings.…”
Section: A P -Plasticity; R -Elastic Recovery; F C -Cohesive Strengthsupporting
confidence: 89%
“…Today, it is generally acknowledged that the abrasion and wet road holding of tyres depend on the glass transition temperature of the rubbers in the tread formulation [12,13]. Increase in T g indicates a reduction in the rate of relaxation processes in the polymer and consequently leads to a reduction in elasticity.…”
Section: A P -Plasticity; R -Elastic Recovery; F C -Cohesive Strengthmentioning
confidence: 99%
“…The T g of carbon black/ HDS and carbon black/HDS/AL filler systems has increased compared to the T g of carbon black counterpart. Keinel and Dizon showed that the polymers with higher T g give greater abrasion loss or poorer abrasion resistance [43].…”
Section: Failure Properties and Rubber Composites Hysteresismentioning
confidence: 99%
“…The precise control of polymer microstructure has still been one of the active research areas in polymer chemistry because polymer microstructure is closely related to the properties of polymeric materials such as rubber products. For example, some investigations have been conducted on the relationship between physical properties of rubber materials and the microstructures of styrene‐butadiene rubber (SBR), which are four monomeric units, 1,4‐ cis , 1,4‐ trans , 1,2‐vinyl and styrene units, thus far . Saito et al reported that antiabrasion, wet skid and rolling resistance properties of tire treads have good relationships with styrene and 1,2‐vinyl contents of the used SBRs 1(c) …”
Section: Introductionmentioning
confidence: 99%